Addressing housing-related social needs for Medicaid beneficiaries: a qualitative assessment of Maryland’s Medicaid §1115 waiver program - Robert DeGrazia; Abdikarin Abdullahi; MaryAnn Mood; Christin Diehl; Ian Stockwell; Craig Evan Pollack (BMC Health Services Research, 2023)
Abstract Background While health care payers are increasingly considering approaches that help support stable and affordable housing for their beneficiaries, experience with these initiatives is limited. Through its §1115 HealthChoice waiver, Maryland Medicaid has begun experimenting with programs designed to pay for housing and tenancy support/case management services. This study investigates barriers and facilitators to the success of Maryland’s pilot program initiative — Assistance in Community Integration Services (ACIS). Methods The study focused on key stakeholders employed by the four Lead Entities that currently participate in the ACIS program. The stakeholders included members of each Lead Entity’s administration, direct service providers, state and local government officials, and case managers from local hospitals. The convenience sample was selected through an initial list of stakeholders and was supplemented using snowball sampling methods. Interviews were audio recorded and turned into transcripts via Otter.ai and then analyzed using NVivo by two independent reviewers. Results A total of 23 interviews were conducted between February 2022 and May 2022, representing a broad range of stakeholders across different Maryland geographies. A total of 4 themes were identified through the course of the interviews. Stakeholders identified difficulty finding housing for the target population in a tight housing market, challenges with communication within the program and with its clients, and problems with non-healthcare providers documenting services for reimbursement. At the same time, ACIS was seen as creating opportunities for organizations to work together across siloes in meeting client needs. Conclusions The findings of this study helps to highlight Medicaid §1115 waivers as a novel approach to using Medicaid funds to support tenancy-based services, such as ACIS and to improve the lives of individuals while reducing healthcare costs. Implementation of the ACIS program in Maryland has been a resounding success in helping individuals obtain and sustain stable housing. However, continued efforts to align capacity with demand, streamline billing and reimbursement and improve communication with clients and across partners will need to be prioritized. The program also highlights the growing need to address root causes of housing insecurity including the limited supply of affordable housing.